NAA10 (N-Alpha-Acetyltransferase 10): A Multifunctional Regulator in Development, Disease, and Cancer - Zeng Quan Yang; Ion John Campeanu; Ivan Lopez; Manaal Syed; Yuanyuan Jiang; Hilda Afisllari (Cells)
NAA10 (N-alpha-acetyltransferase 10) is a pivotal enzyme in eukaryotic cells, serving as the catalytic subunit of the NatA complex, which is responsible for the N-terminal acetylation of approximately 40–50% of the human proteome. Beyond its canonical role in co-translational N-terminal acetylation, NAA10 also acetylates internal lysine residues of various proteins and exerts non-catalytic regulatory functions through diverse protein–protein interactions. Pathogenic variants in NAA10 are linked to a spectrum of developmental disorders, most notably Ogden syndrome, which is characterized by neurodevelopmental delay, cardiac defects, and craniofacial anomalies. In cancer, NAA10 is frequently overexpressed or genomically amplified, where its dysregulation correlates with tumor aggressiveness and poor prognosis. Functional studies implicate NAA10 in regulating cell cycle progression, apoptosis, migration, and other hallmarks of cancer. In this review, we summarize the structure, molecular mechanisms, and physiological functions of NAA10, as well as its roles in human diseases and cancer. We present in silico pan-cancer analyses that highlight its clinical significance and potential downstream pathways. Furthermore, we discuss the therapeutic potential and challenges of targeting NAA10 in cancer, and propose future research directions to better understand its multifaceted roles in health and disease.